PEMBUATAN JARINGAN KOMPUTER BERBASIS MIKROTIK: Yuliadi, Rodianto, M. Julkarnain, Eri Sasmita Susanto, Nawasyarif, Syamsul Bahtiar, Fadli Dzil Ikram - YULIADI, YULIADI; Rodianto, Rodianto; Julkarnain, M.; Susanto, Eri Sasmita; Nawassyarif, Nawassyarif; Bahtiar, Syamsul; Ikram, Fadhli Dzil (Jurnal Pengabdian Rekayasa Sistem, 2023)
Computer network is one means of supporting the activities of a government or private agency. SMAN 3 Praya Central Lombok is a public senior high school located in the Praya district. Community Service Activities (PkM) are one of the tri dharma activities of higher education with the aim of implementing lecturer knowledge and providing students with learning experiences and collaborating in community development activities as a means of implementing and developing science and technology in communities outside the campus. In the PkM which is carried out with the development of a microtic-based Local Area Network (LAN) computer network. Network installation by installing at several predetermined points, namely the Principal's Room, Teacher's Room, Administration Room, Library Room and Computer Laboratory. In a proxy-based computer network used as bandwidth sharing or bandwidth management using a proxy router on each host/user is an important part to do for internet service providers. Bandwidth is the most important part of a network, therefore the amount of bandwidth or bandwidth management is taken into account in order to create fast and flexible access so as to maximize internet connections according to the needs in each section. There is a need for bandwidth management to divide the amount of bandwidth needed.